Testicular Tuberculosis in an HIV Positive Patient Co-infection with Pulmonary Tuberculosis Mimicking Malignancy: A Case Report - Wahyu Agung Purnomo; Tutik Kusmiati; Soedarsono Soedarsono (Jurnal Respirasi, 2020)
Background: Extrapulmonary involvement can be seen in more than 50% of patients with concurrent HIV and tuberculosis (TB). Approximately 7% of those are presented as a rare case, namely testicular TB, with scrotal mass as common clinical manifestation. Testicular TB should be a different diagnosis, especially in areas with a high prevalence rate for TB.Case: A 24-year-old male with HIV positive co-infection with pulmonary TB presented with a progressively increasing painless right testicular swelling of 1-month duration. History of chronic cough was complained, accompanied by loss of appetite and decrease of body weight. There was no history of testicular traumatic accident before. Genital examination was right testicular mass measuring 7cm x 4cm and depletion of right side scrotal skin with pus and necrotic tissue. He had right orchidectomy by an urologist in a private hospital; then an anatomical pathology was examined. The result of the microscopic evaluation showed granuloma inflammation process typical for orchitis tuberculosis. The patient was reactive for HIV and had Mycobacterium tuberculosis (MTB) detected, Rifampicin resistant not recognized as the result of Gene Xpert MTB/RIF assay.Conclusion: Although a rare case, testicular TB should be a different diagnosis when there is a patient with HIV positive concurrent pulmonary TB with scrotal mass as clinical manifestation, especially in areas with a high prevalence rate for TB.